Enhanced RF analog linearity in metal gate modulated heterojunction based uniform TFET for label-free detection of dengue NS1 protein - T, Ranjith Kumar; G, Lakshmi Priya (Scientific reports, 2025)
This work presents a comprehensive investigation of symmetric (HJ-DD-UTFET) and asymmetric Source Drain Heterojunction Dual Dielectric Uniform Tunnel Field-Effect Transistors (A-SD-HJ-DD-UTFET) to achieve enhanced analog/RF, and linearity performance. The A-SD-HJ-DD-UTFET showcases an extremely low OFF current level of 8.124 × 10 –17 A/μm which surpasses the symmetric HJ-DD-UTFET by 5,470 times and presents a high ON–OFF ratio of 2.83 × 10 12 representing a 6,261 times improvement. This enhanced performance occurs because of structural asymmetry which makes it suitable for high-end RF and biosensing purposes while reaching a peak transconductance of 536 µS. For dengue NS1 protein detection (κ = 78.7), the TCAD-driven model of the proposed A-SD-HJ-DD-UTFET biosensor delivers a distinctive label-free detection method, achieving a peak transconductance (g m ) of 577 µS, cut-off frequency (f T ) of 193 GHz, Gain-Bandwidth Product (GBP) of 201 GHz, Transconductance Generation factor (TGF) of 155 V -1 , and gain transconductance frequency product (GTFP) of 25.9 THz. These correspond to improvements of 51.4%, 13.5%, 26.4%, 96.4%, and 45.5%, respectively, over SARS-CoV spike protein detection (κ = 2). The A-SD-HJ-DD-UTFET biosensor also exhibits superior linearity performance during dengue NS1 protein detection through its desirable intercept points, minimal intermodulation distortion, and a well-maintained 1 dB compression point, affirming its potential as a high-speed, label-free RF biosensor for infectious disease Point of Care Testing (POCT) diagnostics.